Association of Antibiotic Exposure With Survival and Toxicity in Patients With Melanoma Receiving Immunotherapy. (15th April 2020) - Mohiuddin, Jahan J; Chu, Brian; Facciabene, Andrea; Poirier, Kendra; Wang, Xingmei; Doucette, Abigail; Zheng, Cathy; Xu, Wei; Anstadt, Emily J; Amaravadi, Ravi K; Karakousis, Giorgos C; Mitchell, Tara C; et al.
Abstract: Background: Gut microbial diversity is associated with improved response to immune checkpoint inhibitors (ICI). Based on the known detrimental impact that antibiotics have on microbiome diversity, we hypothesized that antibiotic receipt prior to ICI would be associated with decreased survival. Methods: Patients with stage III and IV melanoma treated with ICI between 2008 and 2019 were selected from an institutional database. A window of antibiotic receipt within 3 months prior to the first infusion of ICI was prespecified. The primary outcome was overall survival (OS), and secondary outcomes were melanoma-specific mortality and immune-mediated colitis requiring intravenous steroids. All statistical tests were two-sided. Results: There were 568 patients in our database of which 114 received antibiotics prior to ICI. Of the patients, 35.9% had stage III disease. On multivariable Cox proportional hazards analysis of patients with stage IV disease, the antibiotic-exposed group had statistically significantly worse OS (hazard ratio [HR] = 1.81, 95% confidence interval [CI] = 1.27 to 2.57; P <.001). The same effect was observed among antibiotic-exposed patients with stage III disease (HR = 2.78, 95% CI = 1.31 to 5.87; P =.007). When limited to only patients who received adjuvant ICI (n = 89), antibiotic-exposed patients also had statistically significantly worse OS (HR = 4.84, 95% CI = 1.09 to 21.50; P =.04). The antibiotic group had a greater incidence of colitis (HR = 2.14, 95% CI = 1.02 to 4.52; P =.046). Conclusion: Patients with stage III and IV melanoma exposed to antibiotics prior to ICI had statistically significantly worse OS than unexposed patients. Antibiotic exposure was associated with greater incidence of moderate to severe immune-mediated colitis. Given the large number of antibiotics prescribed annually, physicians should be judicious with their use in cancer populations likely to receive ICI.